Implementation of Cloud-based Supply Chain Management Information System for Logistics Optimization - Fauzi, Ahmad; Rahmawati, Siti (PT. Technology Laboratories Indonesia (TechnoLabs), 2025)
This research aims to implement a cloud-based Supply Chain Management Information System (SCMIS) to optimize the logistics process at PT Wijaya Badja Global. The company faces challenges in managing an efficient supply chain, including inter-departmental coordination, inventory tracking, and timely delivery of goods. By utilizing cloud technology, this system is designed to improve visibility, speed, and accuracy in supply chain management. The research methods used include requirements analysis, system design, implementation, and performance evaluation. The results show that the implementation of cloud-based SCMIS is able to reduce logistics costs, improve operational efficiency, and accelerate response time to changes in market demand. In addition, the system also enables better data integration between suppliers, distributors, and customers. Thus, this research contributes to the application of cloud technology for supply chain optimization in the logistics sector, especially at PT Wijaya Badja Global.